Konstitusionalitas Keberadaan Bank Tanah dalam Pengelolaan dan Penguasaan atas Tanah oleh Negara - Permadi, Iwan (Universitas Semarang, 2023)
The purpose of this study is to analyse the existing Land Bank arrangements in Indonesia and the legal implications of its arrangements for the management and control of land by the State. The problem is that the concept of land as state property has harmed the Indonesian constitution that